The rising tide of photographs: Not drowning but waving? - Pollen, Annebella (Captures, 2016)
Concerns about the huge quantities of photographs circulating in digital networks have led some to proclaim that we are now drowning in images. This article surveys these anxieties by examining the work of artists who use photography’s scale, and juxtaposing this with other similar recent photographic practices. Placing such endeavours in historical context challenges received wisdom about the current photographic condition, thus promoting microhistorical methodologies as a means by which apocalyptic generalisations about mass practice can be nuanced.